The Role of Local Communities in Biodiversity Conservation: Challenges and Integration of Local Wisdom with Modern Science - Nurmalasari, Dita; Nuraini, Reny (Journal of Social Science Studies, 2021)
Biodiversity conservation is becoming an increasingly pressing global issue, with many countries recognizing the important role of local communities in environmental conservation. In Indonesia, social forestry is one form of community empowerment in the sustainable management of natural resources. Despite conservation efforts undertaken by local communities, the main problem faced is the imbalance between conservation goals and meeting the economic needs of local communities. To face this challenge, it is important to integrate local wisdom with modern science to create effective solutions. Limited resources, both financial and technical, are often a major barrier for local communities to implement sustainable conservation programs. Social changes, such as urbanization and changing lifestyles, exacerbate the challenge of maintaining a balance between conservation and economic needs. Therefore, collaboration between local communities, scientists and the government is crucial to design conservation programs that consider both environmental sustainability and the economic well-being of the community. By strengthening the capacity of local communities through training, access to technology and financial support, a better balance between conservation and socio-economic needs can be achieved.